Dukungan Keluarga dengan Keberhasilan Pemberian ASI Eksklusif di Desa Sidoarum Godean, Sleman - Margaretha Putri Sariningrum; Yuni Fitriana; Sri Susilowati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2020)
Background: Standard low of suckle on the breast in some countries because decrease of supportbreastfeeding for mother in around area. The problem often come at 2012, in global giving exclusivebreastmilk still under 50%. Family support for breastfeeding that know breastmilk good food for babyis better supported for success breasfeeding. Study preface in Sidoarum Village mention one offactor about giving exclusive breastmilk is a family support.Goal: The goal of the research to know about the relation of family support with sucessful givingexclusive breastmilk in Sidoarum Village Godean Sleman 2016Method: This research is quantitative research, design with descriptive correlation, use crosssectional research. The subject of the study is mother who has baby between 6 to 11 month atFebruary 2016. In selecting sample, its research use cluster random sampling with 48 respondents. Itis analyzed by chi-square and the instrument is used questionnaireResult: The result from 48 responden family support at offer bresfeeding exclusive there are 26respondent (54,2%). The mother was success give breastfeeding such as 38 responden (79,2%).There is any relation between family support with sucessful giving exclusive breastmilk (pvalue=0.000).Conclusion: There is any relation between familly support to sucessful giving exclusive breastmilk inSidoarum Village Godean Sleman 2016. The expect familly giving motivation mother for breasfeedingin order to sucessful giving exclusive breastmilkKeyword: Family Support, exclusive breastmilk.